Depiction of Lugra Saree worn by Koli women folk - Mumbai Archive Project Team (Jio Institute, 2024)
For additional coverage and to ensure it stays in place while working, women typically drape the Lugra saree by taking the pallu (the loose end of the saree) over the shoulder and tucking it at the waist in the back or bringing it around to the front.